1985
DOI: 10.1111/j.1464-410x.1985.tb07021.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Double J Stenting on Unobstructed Ureters. An Experimental and Clinical Study*

Abstract: Upper tract pressure flow studies in four clinically unobstructed ureters with double J stents in situ indicated that urinary flow occurred mainly around the stent and that there was significant vesicorenal pressure transmission. This study examined the dynamics of ureteric urinary flow and morphological effects consequent upon stenting a ureter in vivo. In a porcine model, ureteric intubation caused a rise in intrapelvic pressures, hydroureter, vesicorenal reflux and generalised thickening of the ureteric wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(69 citation statements)
references
References 6 publications
0
64
0
5
Order By: Relevance
“…The increased intrapelvic renal pressure, especially while voiding, explains this greater incidence of pain. Ramsay et al demonstrated in a porcine model that ureteral intubation causes an increase in intrapelvic renal pressure while voiding [10].…”
Section: Discussionmentioning
confidence: 99%
“…The increased intrapelvic renal pressure, especially while voiding, explains this greater incidence of pain. Ramsay et al demonstrated in a porcine model that ureteral intubation causes an increase in intrapelvic renal pressure while voiding [10].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining urine flow with a stent seems to depend mainly on extraluminal flow supported by a double J stent, preventing total ureteral occlusion [5,13]. If the stent could not maintain the extraluminal space, the role of the stent in urine flow rate becomes too small, because the luminal flow out of the total flow in the stented ureter is very small.…”
Section: Luminal and Extraluminal Flow Rates And Patternsmentioning
confidence: 99%
“…Although ureteral stents are inserted to relieve the stagnation of urine flow due to the stenosis or occlusion of the ureter, indwelling of a ureteral stent itself could be a factor of insufficient urine flow [5][6][7] because it prevents peristalsis in the upper urinary tract, as well as results in the loss of effective ureteral peristalsis in the end. Previous studies [8][9][10][11][12] evaluated the urine flow in a stented ureter using the model of a straight ureter and a double J stent.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge both peristaltic and differential pressure has yet not been addressed in the literature of stented ureters. In the presence of a stent, peristalsis is greatly inhibited and is sometimes considered negligible in comparison to the propulsive pressure gradient between the kidney and bladder [2,10,13]. Though, on an all-encompassing scale, just the slightest reflux could result in serious infection, a critical scenario potentially realized in the presence of peristalsis.…”
Section: Introductionmentioning
confidence: 99%